2021
DOI: 10.3389/fpubh.2020.582234
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Morbidity in the Older Person: An Examination of Polypharmacy and Socioeconomic Status

Abstract: There has been increased focus on clinically managing multi-morbidity in the older population, but it can be challenging to find appropriate paradigm that addresses the socio-economic burden and risk for polypharmacy. The Commission on Social Determinants of Health (CSDH) has examined the need for institutional change and the parallel need to address the social causes of poor health. This study explored three potential interventions namely, meaningful information from electronic health records (EHR), social pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 43 publications
2
8
0
Order By: Relevance
“…General trends have shown that patients with lower socioeconomic status and older-age patients often have multiple comorbidities which may affect their length of stay. However, the general trends that we see in our study have also been shown to be true in other studies analyzing different medical conditions [27].…”
Section: Discussionsupporting
confidence: 89%
“…General trends have shown that patients with lower socioeconomic status and older-age patients often have multiple comorbidities which may affect their length of stay. However, the general trends that we see in our study have also been shown to be true in other studies analyzing different medical conditions [27].…”
Section: Discussionsupporting
confidence: 89%
“…The influence of the socioeconomic and political context on older adults with multimorbidity is an underexplored topic in the literature. 42 As for patient organizations, we strongly encourage novel collaborations and initiatives advocating for those who live with multiple chronic conditions and raising awareness of 'multimorbidity' and its impact on people and society. 38 By joining forces, the organizations can help the growing group of multimorbid patients manage their different conditions and navigate the system that will otherwise potentially drain their already limited resources.…”
Section: Discussionmentioning
confidence: 99%
“…When evaluating the quality of life, health is generally considered as the most relevant factor; however, there are other aspects that should be considered and that are equally important to ensure wellbeing [ 46 ].…”
Section: Ageing and The Elderlymentioning
confidence: 99%